The impact of using the lecture method on teaching english at university - Khalid Abdul baki; Muhamad Suhaimi; Asmaa AlSaqqaf; Wafa Jawad (2018)
This paper deals with the effectiveness of the lecture method of teaching at university inimproving students’ linguistic and academic skills. Research on English languageteaching at universities and colleges in Oman reveal that a high rate of students whofinish secondary schools and join higher education institutions could face difficulties inusing the English language to meet their personal, social, academic, and career needsefficiently and appropriately. Lectures are popular among university academics forsome reasons such as that they are economical in terms of planning, flexible as they canbe applied to most content areas and also simple to implement in class. On the otherhand, critics argue that lecturing is principally a one-way method of communicationthat does not involve significant students’ participation. The objectives of this researchstudy are to find out students’ views and opinions of the use of the lecture method inteaching English as well as its strengths and weaknesses. The findings showed thatalthough majority of respondents indicated that they had learned a lot from the lecturematerial, a number of respondents refer to the lack of motivation to participate duringthe lecture. Meanwhile, few indicated that there is an opportunity to interact during thelecture although the lecturer is the only authority as he dictates his points of view inclass. The implications could be that some lecturers at university may find it the righttime for them to accept the fact that actual participation of students in their learning is asignificant practice to achieve the goals set by their educational institutions. It certainlydoes not affect the role of the lecturer as an educator and leader. On the contrary, itcould create an active and enjoyable atmosphere for exchanging knowledge andimproving skills.